2014
DOI: 10.1103/physrevd.89.083510
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous creation of the universe from nothing

Abstract: An interesting idea is that the universe could be spontaneously created from nothing, but no rigorous proof has been given. In this paper, we present such a proof based on the analytic solutions of the Wheeler-DeWitt equation (WDWE). Explicit solutions of the WDWE for the special operator ordering factor p=-2 (or 4) show that, once a small true vacuum bubble is created by quantum fluctuations of the metastable false vacuum, it can expand exponentially no matter whether the bubble is closed, flat or open. The e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 19 publications
(19 reference statements)
3
51
0
1
Order By: Relevance
“…The results are significant, for [10] presents a rigorous proof that the universe could be spontaneously and irreversibly created from nothing, and that after-wards it proceeds to an inflationary epoch. It is also shown that the exponential expansion stops when the scale factor grows sufficiently large, no matter whether it is closed, open, or flat.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The results are significant, for [10] presents a rigorous proof that the universe could be spontaneously and irreversibly created from nothing, and that after-wards it proceeds to an inflationary epoch. It is also shown that the exponential expansion stops when the scale factor grows sufficiently large, no matter whether it is closed, open, or flat.…”
Section: Discussionmentioning
confidence: 85%
“…A recent work [10], which uses this method, shows that the universe can spontaneously and irreversibly be created from nothing, and also that it can then pass over to an inflationary epoch. The authors first obtain the solutions to the WD equation for an empty universe, with closed, open or flat space sections, when a particular operator ordering is chosen in it.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of non-zero potential a difficulty arises in that the eigenfunctions are not normalisable. We compute an expression for the fractional rate of change 2 The de Broglie-Bohm formulation has been used in quantum cosmology by a number of authors, such as by Pinto-Neto and collaborators in connection with bouncing models [25,27], by Pinto-Neto, Santos and Struyve [26] and Valentini [34] in relation to inflation, and most recently by He, Gao and Cai in work on the mathematical foundations of big-bang cosmology [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, if the assumption that the balance of vacuum energy and gravitational energy takes place only for times larger than the Planck time is correct, it is the time-energy uncertainty principle that acts as the engine in generating the initial conditions necessary for the creation of vacuum energy and hence to the expansion of the universe. Indeed, it has been even suggested that the initial primordial matter (energy) necessary for the creation of the universe also came into being thanks to the time-energy uncertainty principle [14].…”
Section: Discussionmentioning
confidence: 99%